Balance Between Rapid Delayed Rectifier K+ Current and Late Na+ Current on Ventricular Repolarization: An Effective Antiarrhythmic Target?. (April 2020) - Hegyi, Bence; Chen-Izu, Ye; Izu, Leighton T.; Rajamani, Sridharan; Belardinelli, Luiz; Bers, Donald M.; Bányász, Tamás
Abstract : Background: Rapid delayed rectifier K + current (IKr ) and late Na + current (INaL ) significantly shape the cardiac action potential (AP). Changes in their magnitudes can cause either long or short QT syndromes associated with malignant ventricular arrhythmias and sudden cardiac death. Methods: Physiological self AP-clamp was used to measure INaL and IKr during the AP in rabbit and porcine ventricular cardiomyocytes to test our hypothesis that the balance between IKr and INaL affects repolarization stability in health and disease conditions. Results: We found comparable amount of net charge carried by IKr and INaL during the physiological AP, suggesting that outward K + current via IKr and inward Na + current via INaL are in balance during physiological repolarization. Remarkably, IKr and INaL integrals in each control myocyte were highly correlated in both healthy rabbit and pig myocytes, despite high overall cell-to-cell variability. This close correlation was lost in heart failure myocytes from both species. Pretreatment with E-4031 to block IKr (mimicking long QT syndrome 2) or with sea anemone toxin II to impair Na + channel inactivation (mimicking long QT syndrome 3) prolonged AP duration (APD); however, using GS-967 to inhibit INaL sufficiently restored APD to control in both cases. Importantly, INaL inhibition significantly reduced the beat-to-beat and short-term variabilities of APD. Moreover, INaL inhibition also restored APD and repolarization stability in heart failure. Conversely, pretreatment with GS-967 shortened APD (mimicking short QT syndrome), and E-4031 reverted APD shortening. Furthermore, the amplitude of AP alternans occurring at high pacing frequency was decreased by INaL inhibition, increased by IKr inhibition, and restored by combined INaL and IKr inhibitions. Conclusions: Our data demonstrate that IKr and INaL are counterbalancing currents during the physiological ventricular AP and their integrals covary in individual myocytes. Targeting these ionic currents to normalize their balance may have significant therapeutic potential in heart diseases with repolarization abnormalities. Abstract : Supplemental Digital Content is available in the text.